Flexibility approach in the runway pavement using flemanco method - Paslawski, Jerzy (Transport, 2008)
The pressing problems of managing construction processes reveal themselves in discrepancies between plan and execution which seems to result in considerable measure from dependence on the changing environment. High variability, dynamics and uncertainty of execution conditions generate disturbances which could be avoided by applying flexibility ‐ creating a range of executive options enabling adjustment to changing environmental conditions. The principal advantages of implementing the proposed FLEMANCO (FLExibility MANagement in the COnstruction industry) method include better consistency between planning and an actual course of execution, lower changes in costs and execution time by considering various scenarios of execution conditions, the possibility of loss prevention and taking advantage of opportunities connected with the changing environment etc. The presented example concerns concreting a runway, although similar problems occur in concreting roads, yards, bridges as well as erecting high buildings, earthworks etc.First published online: 27 Oct 2010